Los acuerdos en la gestión administrativa de Carmen de Carupa y la ausencia de planeación, seguimiento y evaluación de la misma (2017)
For optimum administrative management of the territorial entities, compliance with the planning, monitoring and evaluation processes is required. These processes have not been fully applied in the Municipality of Carmen de Carupa - Cundinamarca, since the management of the Municipality was not followed or evaluated, in relation to the programs contained in the Development Plan 2012 - 2015, partially violating norms By article 339 and SS of the CP and its organic law. However, it is proper to state that this legal situation can be improved through management agreements executed from two levels; The first level between the mayor's office and the government, under the principle of autonomy and second level, management agreements between the mayor and his officials, so that the latter fulfill their office as autonomous units but articulated in the achievement of objectives in common.